Tourism Experience and Tourist Satisfaction of Domestic Tourists in Pagar Alam - Taslim, M.; Karo, Pelliyezer Karo; Badollahi, Muh. Zainuddin (Newinera Publisher, 2023)
This study aims to discuss tourist experiences and tourist satisfaction during a vacation or tour in Pagar Alam. The study used a quantitative method with simple linear regression analysis. The sampling technique used a simple random sampling method with primary data collected through a questionnaire to 130 respondents. The memorable tourism experience variable is represented by seven indicators in the form of hedonism, local culture, novelty, refreshment, involvement, knowledge, and meaningfulness, while the tourism satisfaction variable is represented by four indicators in the form of price, product convenience, service treatment, and positive feeling. The study results showed that the memorable tourism experience variable positively and significantly influences the tourist experience. The desire of tourists to always share their travel experiences through social media provides the highest indication that this has two impacts at once, both positive and negative. The level of sharing positive experiences is a strong indicator of the success of achieving tourist satisfaction during travel.